Pelanggaran Maksim Kesantunan Dalam Novel Nijuushi No Hitomi Karya Sakae Tsuboi - Ariana, I Nengah; Pradhana, Ngurah Indra; Yuliani Giri, Ni Luh Kade (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p11, 2018)
This research entitled “Violation of  politeness maxim in Nijuushi no Hitomi’s Novel by Sakae Tsuboi”. This research aims to find out the kind speech act and type of violated conversation which got violated in Nijuushi no Hitomi’s Novel by Sakae Tsuboi. The data analyzed using descriptive method. The theories used for analyzing are speech acts (illocutionary acts) theory by Searle (1969) and the politeness principle theory by Leech (1983). Based on the analysis that has been done, there are v iolation of politeness maxim , such as (1) tact maxim (six data that aims for requesting, commanding, prohibiting, inviting and persuading), (2) generosity maxim (one data that aims for mocking), (3) approbation maxim (eight data that aims for mocking, blaming and naming) (4) agreement maxim (four data that aims for lying, advising, resigning and dismissing) (5) sympathy maxim (two data that aims for commanding and mocking).